The first report of RPSA polymorphisms, also called 37/67 kDa LRP/LR gene, in sporadic Creutzfeldt-Jakob disease (CJD) - Jeong Byung-Hoon; Carp Richard I; Choi Eun-Kyoung; Lee Yun-Jung; Jin Hyoung-Tae; Yun Jisuk; Kim Yong-Sun (BMC, 2011)
Abstract Background Although polymorphisms of PRNP, the gene encoding prion protein, are known as a determinant affecting prion disease susceptibility, other genes also influence prion incubation time. This finding offers the opportunity to identify other genetic or environmental factor (s) modulating susceptibility to prion disease. Ribosomal protein SA (RPSA), also called 37 kDa laminin receptor precursor (LRP)/67 kDa laminin receptor (LR), acts as a receptor for laminin, viruses and prion proteins. The binding/internalization of prion protein is dependent for LRP/LR. Methods To identify other susceptibility genes involved in prion disease, we performed genetic analysis of RPSA. For this case-control study, we included 180 sporadic Creutzfeldt-Jakob disease (CJD) patients and 189 healthy Koreans. We investigated genotype and allele frequencies of polymorphism on RPSA by direct sequencing or restriction fragment length polymorphism (RFLP) analysis. Results We observed four single nucleotide polymorphisms (SNPs), including -8T>C (rs1803893) in the 5'-untranslated region (UTR) of exon 2, 134-32C>T (rs3772138) in the intron, 519G>A (rs2269350) in the intron and 793+58C>T (rs2723) in the intron on the RPSA. The 519G>A (at codon 173) is located in the direct PrP binding site. The genotypes and allele frequencies of the RPSA polymorphisms showed no significant differences between the controls and sporadic CJD patients. Conclusion These results suggest that these RPSA polymorphisms have no direct influence on the susceptibility to sporadic CJD. This was the first genetic association study of the polymorphisms of RPSA gene with sporadic CJD.